Pérdida del rol paterno – filial y su incidencia en las conductas violentas de estudiantes de noveno año de educación básica de la Unidad Educativa Babahoyo en el año 2019 - Puya Muñoz, Kathiusca Mariuxi (2019)
Violent behaviors in students are due to many factors that condition their life and that generally happen in their homes, with this perception you can not leave aside what happens in educational institutions that also has their contribution in this problem, In this research work an important factor is addressed that little is taken into account in educational institutions such as the loss of the paternal-filial role, the same that once it is presented, it becomes difficult for the mother or those who are charge of their care to control, assuming students their control and command, which should be a reason for study as in the present work. For the realization of this study, the non-experimental transversal design was chosen, with a documentary and field modality, a descriptive, explanatory and exploratory type of research, aimed at students, teachers and parents of the ninth year of basic education, to who were applied data collection techniques such as interviews and surveys, obtaining results such as the loss of parental role in some households, which leads to a deterioration in the school behavior of students, becoming violent behaviors that unbalance the process of teaching learning and put the other students at risk, for which the following alternative proposal is proposed Systemic Family Therapy Program with the ninth year students of basic education of the Babahoyo Educational Unit